An overview about the impact of hinge region towards the anticancer binding affinity of the Ck2 ligands: a quantum chemical analysis. Issue 15 (13th October 2019) - Deepa, P.; Thirumeignanam, D.; Kolandaivel, P.
Abstract: Casein kinase 2 (CK2) is extremely preserved and universally uttered serine/threonine kinase, vital for cellular feasibility. The present study aimed to analyse the binding strength of CK2 ligands specifically in the hinge region, as it is aware that most of the existing drugs are targeted to bind the hinge of the corresponding protein. The analysis will give a clear picture about the role of hinge region with ligand, which will be useful for scientist community in drug designing. To predict the binding strength of CK2 ligands, the role of halogen bond, hydrogen bond interaction at the hinge region was depicted in detail through interaction energy calculations at M062Z/def2-QZVP level of theory. Highest occupied molecular orbital (HOMO) map plotted for CK2 ligands gives a clear pictorial representation of orbitals, which induce for interaction. Ligand properties discussed in detail through Lipinski's five rules predict that almost all the ligands satisfy the rule, except 3KXG, which violates Lipinski's two rules, i.e. molecular mass exceeds 500 Da, i.e. 512.61 Da, and Log P value is high of 5.09. The natural bond orbital analysis deliberates that the hydrogen/halogen bonds figuring out within the complexes are observed to have moderate stabilization energy, but those hydrogen/halogen bonds that exist with close contacts have high stabilization energy. Overall, this computational work will give an understandable depiction for modelling anticancer ligands along the hinge region in CK2 protein; also, it will give a new path for the choice of side chains on the ligand. Communicated by Ramaswamy H. Sarma